1991
DOI: 10.1002/ijc.2910470327
|View full text |Cite
|
Sign up to set email alerts
|

Differential influence of organ site on three subpopulations of a single mouse mammary tumor at two distinct steps in metastasis

Abstract: Tumor subpopulations 66c14, 168FARN, and 4T07 are drug-resistant variants selected from sister subpopulations derived from a single mouse mammary tumor. These subpopulations are heterogeneous in their capacities to form experimental metastatic growth in the lungs and liver. Initial survival kinetics of arrested cells, determined by the clearance of 125IUdR-labelled cells, and subsequent growth rates, determined by sequential recovery of clonogenic tumor cells from occult metastases, both correlated with organ-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
61
0

Year Published

1993
1993
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(64 citation statements)
references
References 25 publications
3
61
0
Order By: Relevance
“…A highly malignant BALB/c tumor cell line (4T1) was used in this study. 12 Eleven BALB/c (Taconic Farms, Germantown, NY) female mice (6-to 8-weeks old) were injected subcutaneously at the nipple of the 5th mammary gland on one side, with a suspension of 1 3 10 5 4T1 tumor cells. All mice developed tumor nodules at the injection site.…”
Section: Animal Experimentsmentioning
confidence: 99%
“…A highly malignant BALB/c tumor cell line (4T1) was used in this study. 12 Eleven BALB/c (Taconic Farms, Germantown, NY) female mice (6-to 8-weeks old) were injected subcutaneously at the nipple of the 5th mammary gland on one side, with a suspension of 1 3 10 5 4T1 tumor cells. All mice developed tumor nodules at the injection site.…”
Section: Animal Experimentsmentioning
confidence: 99%
“…In order for tumour cells injected intravenously to form lung colonies, the cells must be arrested and retained in the lung, extravasate, and replicate in lung parenchyma. Previous studies with line 4T07 using similar colony-forming assays have shown that it arrests and grows in lung in a characteristic time-dependent manner which can be related to these several steps of metastasis (Aslakson et al, 1991a(Aslakson et al, , 1991b. The majority (>80%) of line 4T07 cells injected i.v.…”
Section: Discussionmentioning
confidence: 92%
“…Agents which inhibit metastasis are usually evaluated by determining their effect on the final outcome of this metastatic sequence, either by the overall effect on survival or by comparing the number or size of metastatic nodules which develop in treated vs control animals. By using a series of mouse mammary tumour cell lines with selectable markers, we have been able to follow the development of experimental lung and liver metastases from cell injection through the appearance of visible nodules (Aslakson et al, 1991a), and have described immunological treatments which inhibit lung colonisation at two different steps in the metastatic sequence (Aslakson et al, 1991b). These tumour cell lines were selected from sister subpopulations derived from a single mouse mammary tumour.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Heterogeneity of tumour cell subpopulations and their cooperation in contributing to malignant tumour progression have been studied in only a few systems (Aslakson et al, 1991;Hart & Saini, 1992;Heppner & Miller, 1983;Maghazachi et al., 1988;Miller et al, 1980;Miller & Heppner, 1990). Interactions among subpopulations of tumour cells could very well determine the outcome of metastasis (Hart et al, 1989;Miller & Heppner, 1990).…”
mentioning
confidence: 99%